Comparative Assessment of 3D Surface Scanning Systems in Breast Plastic and Reconstructive Surgery. (October 2013) - Patete, Paolo; Eder, Maximilian; Raith, Stefan; Volf, Alexander; Kovacs, Laszlo; Baroni, Guido
In this work, we compared accuracy, repeatability, and usability in breast surface imaging of 2 commercial surface scanning systems and a hand-held laser surface scanner prototype coupled with a patient's motion acquisition and compensation methodology. The accuracy of the scanners was assessed on an anthropomorphic phantom, and to evaluate the usability of the scanners on humans, thorax surface images of 3 volunteers were acquired. Both the intrascanner repeatability and the interscanner comparative accuracy were assessed. The results showed surface-to-surface distance errors inferior to 1 mm and to 2 mm, respectively, for the 2 commercial scanners and for the prototypical one. Moreover, comparable performances of the 3 scanners were found when used for acquiring the breast surface. On the whole, this study demonstrated that handheld laser surface scanners coupled with subject motion compensation methods lend themselves as competitive technologies for human body surface modeling.